The Civil Liability of Hospitals for Malpractice Committed by Healthcare Personnel Resulting in Baby Switched at Birth Incidents - Tanaya, Velliana; Putri, Intan Indriani (Jurnal IUS Kajian Hukum dan Keadilan, 2025)
Justice serves as a fundamental goal in the legal framework governing healthcare, ensuring that victims of medical malpractice receive proper redress. This study examines the civil liability of hospitals in cases of baby-switched-at-birth incidents due to medical negligence. Despite clear legal provisions, victims often face challenges in obtaining fair accountability. Hospitals, as primary healthcare providers, are responsible for upholding professional standards to prevent malpractice and ensure patient safety. The failure to adhere to these standards constitutes an unlawful act (PMH) under Indonesian civil law, obligating hospitals to compensate for material and immaterial damages. However, inconsistencies in the implementation of patient protection laws hinder the realization of justice. Through a normative-empirical legal analysis, this study highlights the necessity of strengthening legal certainty, enforcing accountability mechanisms, and promoting non-litigation dispute resolution methods to uphold justice for affected patients. Achieving justice in medical malpractice cases requires a balanced approach between legal enforcement and ethical considerations to protect patients' rights effectively.